Spatiotemporal control of cardiac anisotropy using dynamic nanotopographic cues. (April 2016) - Mengsteab, Paulos Y.; Uto, Koichiro; Smith, Alec S.T.; Frankel, Sam; Fisher, Elliot; Nawas, Zeid; Macadangdang, Jesse; Ebara, Mitsuhiro; Kim, Deok-Ho
Abstract: Coordinated extracellular matrix spatiotemporal reorganization helps regulate cellular differentiation, maturation, and function in vivo, and is therefore vital for the correct formation, maintenance, and healing of complex anatomic structures. In order to evaluate the potential for cultured cells to respond to dynamic changes in their in vitro microenvironment, as they do in vivo, the collective behavior of primary cardiac muscle cells cultured on nanofabricated substrates with controllable anisotropic topographies was studied. A thermally induced shape memory polymer (SMP) was employed to assess the effects of a 90° transition in substrate pattern orientation on the contractile direction and structural organization of cardiomyocyte sheets. Cardiomyocyte sheets cultured on SMPs exhibited anisotropic contractions before shape transition. 48 h after heat-induced shape transition, the direction of cardiomyocyte contraction reoriented significantly and exhibited a bimodal distribution, with peaks at ∼45 and −45° (P < 0.001). Immunocytochemical analysis highlighted the significant structural changes that the cells underwent in response to the shift in underlying topography. The presented results demonstrate that initial anisotropic nanotopographic cues do not permanently determine the organizational fate or contractile properties of cardiomyocytes in culture. Given the importance of surface cues in regulating primary and stem cell development, investigation of such tunable nanotopographies may have important implications for advancing cellular maturation and performance in vitro, as well as improving our understanding of cellular development in response to dynamic biophysical cues.